Tilapia viscera protein hydrolysate maintain regulatory T cells and protect acute lung injury in mice challenged with lipopolysaccharide - Putut Har Riyadi; Romadhon Romadhon; Apri Dwi Anggo; Mochammad Fitri Atho'illah; Muhaimin Rifa'i (Journal of King Saud University: Science, 2022)
Objectives: The utilization of fish by-products through hydrolysis methods may produce a high-grade product that increases its economic value and reduces pollution. Tilapia Viscera Protein Hydrolysate (TVPH) is reported to have a positive impact on health. However, there is a lack of evidence for the interplay of regulatory T cells (Tregs) and neutrophils in acute lung injury (ALI) influenced by TVPH. Our study investigated the implication of TVPH on Tregs and its protective effect on ALI in mice challenged with lipopolysaccharide (LPS). Methods: Thirty-six male Balb/C mice were randomized into six groups: untreated, LPS, dexamethasone (DEX) + LPS, and TVPH at doses 150, 300, 450 mg/kg BW, respectively + LPS. Mice were challenged with LPS after seven days of treatment via intraperitoneal injection. After 6 h, mice were sacrificed. Spleen was harvested for flow cytometry analysis, and lung was collected for histological and immunofluorescence analysis. Tregs was labelled as CD4+CD25+CD62L+, CD4+CD25+IL-10, and CD4+CD25+TGF-β+. Neutrophil activation was labeled as a combination of CD66a and MPO antibodies. Results: The CD4+CD25+CD62L+ subsets finding as well as CD4+CD25+IL-10+, CD4+CD25+TGF-β+ subsets, the expression of CD66a and MPO, and lung histopathological imaging confirmed that TVPH and DEX attenuate LPS-induced ALI significantly (p < 0.05). Conclusion: Our finding proposed that TVPH protects LPS-induced ALI through maintaining neutrophils and Tregs. TVPH might be a promising food nutraceutical candidate by reducing the impact of inflammation.